Vagus nerve stimulation in children with drug-resistant epilepsy of monogenic etiology - Xie, Han; Ma, Jiayi; Ji, Taoyun; Liu, Qingzhu; Cai, Lixin; Wu, Ye (Frontiers in Neurology, 2022)
Vagus nerve stimulation (VNS) is an effective treatment for drug-resistant epilepsy (DRE). The present study evaluated the efficacy of VNS in pediatric patients with DRE of monogenic etiology. A total of 20 patients who received VNS treatment at our center were followed up every 3 months through outpatient visits or a remote programming platform. The median follow-up time was 1.4 years (range: 1.0–2.9). The rate of response to VNS at 12 months of follow-up was 55.0% (11/20) and the seizure-free rate was 10.0% (2/20). We found that 75.0% (3/4) of patients with an SCN1A variant had a >50% reduction in seizure frequency. Patients with pathogenic mutations in the SLC35A2, CIC, DNM1, MBD5, TUBGCP6, EEF1A2, and CHD2 genes or duplication of X q28 (MECP2 gene) had a >50% reduction in seizure frequency. Compared with the preoperative electroencephalography (EEG), at 6, 12, 18, and 24 months after stimulator implantation, the percentage of the patients whose background frequency increased >1.5 Hz was respectively, 15.0% (3/20), 50.0% (10/20), 58.3% (7/12) and 62.5% (5/8); the percentage of the patients whose interictal EEG showed a >50% decrease in spike number was respectively 10% (2/20), 40.0% (8/20), 41.6% (5/12) and 50.0% (4/8). In the 9 patients with no response to VNS treatment, there was no difference in terms of spike number and background frequency between preoperative and postoperative EEG. Five of the 20 children (25.0%) reached new developmental milestones or acquired new skills after VNS compared to the preoperative evaluation. The efficacy of VNS in pediatric patients with DRE of monogenic etiology is consistent with that in the overall population of pediatric DRE patients. Patients with Dravet syndrome (DS), tuberous sclerosis complex (TSC), or Rett syndrome/MECP2 duplication syndrome may have a satisfactory response to VNS, but it is unclear whether patients with rare variants of epilepsy-related genes can benefit from the treatment.